Seasonal Volatile Emission Patterns of the Endemic New Zealand Shrub Dracophyllum subulatum on the North Island Central Plateau - Effah, Evans; Barrett, D. Paul; Peterson, Paul G.; Potter, Murray A.; Holopainen, Jarmo K.; Clavijo McCormick, Andrea (Frontiers in Plant Science, 2021)
Volatile organic compounds (VOCs) produced by plants are essential indicators of their physiological response to environmental conditions. But evidence of natural variation in VOC emissions and their contributing factors is still limited, especially for non-cultivated species. Here we explored the natural volatile emissions of Dracophyllum subulatum Hook.f., an endemic shrub to the North Island Central Plateau of New Zealand, and determined some environmental factors driving the plant’s emissions. Volatile emissions of D. subulatum were measured on four separate occasions from December 2017 to September 2018 using the “push-pull” headspace sampling technique and analyzed using gas chromatography-mass spectrometry (GC-MS). D. subulatum was classified based on the volatiles measured on each sampling occasion using linear discriminant analysis (LDA). On each sampling occasion, we also recorded and compared ambient air temperature, herbivory damage, total soil nitrogen (N), available phosphorus (P), potassium (K) and soil moisture content. The relationship between environmental variables that differed significantly between sampling occasions and volatile emissions were estimated using generalized linear models (GLMs). Based on VOCs measured on each sampling occasion, we were able to distinguish different chemical profiles. Overall, we found that total emission and the relative proportions of all major chemical classes released by D. subulatum were significantly higher during summer. The GLMs reveal that differences in environmental factors between the four sampling occasions are highly associated with changing emissions. Higher temperatures in summer had a consistently strong positive relationship with emissions, while the impacts of soil moisture content, P and K were variable and depended on the chemical class. These results are discussed, particularly how high temperature (warming) may shape volatile emissions and their impact on plants’ ecology.